2019
DOI: 10.11648/j.sjee.20190704.16
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Water-based Drilling Fluids—A High Efficiency Muds Achieving Superior Shale Stability While Drilling Deepwater Well with HPHT in South China Sea

Abstract: In deepwater drilling operation, low temperature, high pressure, gas hydrate, narrow density window are the major challenges for drilling fluids to meet, and with the increasing depth drilled, high temperature and high pressure condition was occurred in deepwater well. In the other side, Oil based muds (OBM) and synthetic based muds (SBM) are limited in using because of the strict environment rules in the South China Sea. In deepwater HTHP well, shale hydration, dispersion and Equivalent Circulation Density (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The mud displayed better performance by excellent shale stability, clay inhibition, lubricity, and high rate of penetration (ROP). The mud showed lower cost due to no issue caused during the drilling operation [5].…”
Section: Mud Properties Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The mud displayed better performance by excellent shale stability, clay inhibition, lubricity, and high rate of penetration (ROP). The mud showed lower cost due to no issue caused during the drilling operation [5].…”
Section: Mud Properties Modificationmentioning
confidence: 99%
“…Similarly, in South China's deepwater well drilling operation, a high-efficiency mud system was determined to be acceptable, and the well application revealed that the selected mud is an excellent alternative to OBM or SBM [5]. HPWBM has been successfully deployed in different fields in Dubai, which contain higher reactive clays and have reached higher degrees of inclination [25].…”
Section: Field Applications Of High-performance Wbmsmentioning
confidence: 99%
See 1 more Smart Citation
“…developed PERFORMAX, a high-performance water-based drilling fluid system for deepwater drilling, in which the filter loss reducer MAX-TROL is a sulfonated resin that acts as a high-temperature and high-pressure filter loss reducer through its own plugging effect. CNOOC has introduced a soil-phase free, strongly inhibited, high performance deepwater water-based drilling fluid system HEM, which was mainly developed by Jiansheng Luo and Huike Li [9] . The filtration loss reducer PF-FLOTRO is a kind of temperature-resistant starch, which reduces the filtration loss by increasing viscosity and lifting cut.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, formulations of drilling fluids play an important role in drilling within HPHT environments. Therefore, oil-based drilling fluids (OBDF) have been repeatedly used in HPHT drilling fluid systems, where they have been shown to be effective in shale drilling in HPHT downhole environments [23]. However, OBDF is toxic for marine species [24] and involves a high cost [25] because it is mostly made up of diesel oil [26].…”
Section: Introductionmentioning
confidence: 99%